MORPHOLOGICAL AND SYNTACTIC ANALYSIS OF THE STRUCTURE OF MEDICAL TERMINOLOGY IN THE ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
Abstract: The most effective units within the medical terminology system are considered in the field of English medical terminology. The formation of terms, especially the structure of terminological units, is considered the most important aspect in the process of filling in learned terminology. This article discusses the morphological and syntactic analysis of forming English and Uzbek medical terms that have been studied and researched. A terminological phrase is a multi-component, semantically integral combination of terms that results from the combination of two, three or more terminological components